MORPHOLOGY OF SURFACE AND COVERINGS STRUCTURE AS APPRAISALS RATING OF COMPOSITION MATERIALS EFFICIENCY - V. N. Kovalevskij; A. V. Kovalevskaja; A. V. Zhuk; S. V. Grigorjev; A. V. Rulkevich; I. V. Fomihina (Литьë и металлургия)
Investigations of morphology of surface deterioration of sintered powders with covering are reflected. It is shown that formation of structure and characteristics of composite material is determined considerably by state of the surface and structure of particles covering.